Zintegrowany system zarządzania jakością, ochroną środowiska oraz bezpieczeństwem i higieną pracy - Sus-Januchowska, Aleksandra (An integrated management system of quality, environmental protection, and work safety, 2006)
The purpose of this article is to present an integrated management system of quality, environmental protection, and work safety. This article introduces the three-point management system which is mentioned in the title: quality (according to ISO 9001:2000), environmental protection (according to ISO 14001:2004), and work safety (according to PN-N 18001:1999). In the present paper are also shown ways of integrating this management system, a general method for implementing the system once it is integrated - an implementation which is based on the process approach - and the advantages of the application. It should be noted that this model is the most beneficial one for an organization to use, because it presents the structures more clearly, improves the mechanism for continuous improvement, and allows a complex approach to all of the problems in an organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 314-325